Use of screening nerve conduction studies for predicting future carpal tunnel syndrome. Issue 2 (February 1997) - Werner, R A; Franzblau, A; Albers, J W; Buchele, H; Armstrong, T J
Abstract : OBJECTIVE: To determine if an abnormal sensory nerve conduction study consistent with median mononeuropathy in asymptomatic workers was predictive of future complaints of the hand or finger suggestive of carpal tunnel syndrome. METHODS: This was a case-control study of over 700 active workers at five different work sites: four sites involved manufacturing workers and one site represented clerical workers. Patients' reports of symptoms of pain, numbness, tingling, or burning in the hand or finger that lasted more than one week or occurred three or more times after the initial screening were investigated. 77 cases were defined as asymptomatic workers with electrodiagnostic findings of median mononeuropathy in either hand based on a comparison of median and ulnar sensory evoked peak latencies. A difference > or = 0.5 ms was defined as abnormal; a normal difference was < or = 0.2 ms. Controls were asymptomatic age, and sex matched workers with normal nerve conduction studies in both hands. Follow up questionnaires were completed 17 (SD 6) months later. RESULTS: The follow up participation rate was 72%. Cases had a 12% risk of developing symptoms during the follow up period compared with 10% in the control group, chi 2 = 0.12, P = 0.73. CONCLUSIONS: Abnormal median sensory nerve conduction studies in asymptomatic workers were not predictive of future hand or fingers complaints and if used for preplacement screening among active workers this should be done with caution.